TROUBLESHOOTING BASEL II: THE ISSUE OF PROCYCLICALITY - Kurti Laszlo - Adam; Bordas Eszter; Benyovszki Annamaria; Szodorai Melinda (Annals of the University of Oradea: Economic Science, 2011)
A widespread concern about Basel II capital requirements is that it might amplify business cycle fluctuations, forcing banks to restrict their lending when the economy goes into recession. Under the IRB approach of Basel II, capital requirements are increasing functions of the probability of default (PD), loss given default (LGD) and exposure at default (EAD) parameters estimated for each borrower, and these inputs are likely to rise in economic downturns. In this paper, we compare two alternative procedures that are designed to somehow moderate the procyclical effects induced by Basel II - type capital regulation. The starting points of our analysis consist Jokivuolla, Kiema and Vesala (2009) and Repullo and Suarez (2009), who both examined the impact of regulatory capital's procyclical effects. It's vital to note remarks of Caprio (2009), that is, making regulatory capital levels countercyclical could worsen the state of an economy during a recession. As we do not have access to the Romanian Central Credit Register database, we compute a model-economy that stands as a proxy for the Romanian firms' sector. Our simulated Romanian economy can be characterised by all Romania-specific macroeconomic controls. Then we estimate a model of PDs during the period 2000 - 2010, and based on the estimated probabilities of default we compute the corresponding series of Basel II capital requirements. After the diagnosis of procyclicality, we analyze two procedures that try to mitigate the cyclical effects of capital regulation: smoothing the output of the Basel II formula, and smoothing the input, by construction of through-the-cycle (TTC) PDs. The comparison of the different procedures is based on the criterion of minimizing the root mean square deviations of each adjusted series. Our results show that the best ways to moderate procyclicality are either to smooth the input of the Basel II formula by using through-the-cycle PDs, or to smooth the output with a multiplier based on GDP growth. We conclude that the GDP-based smoothing may be more efficient than the use of TTC PDs in terms of simplicity and transparency. In terms of the GDP adjustment, regulatory capital levels should increase with approx. 1,31% during an economic growth period and decrease with 4,03% during a recession, in order to mitigate the cyclical effects induced by Basel II - type capital regulation.